2014
DOI: 10.1021/la404947j
|View full text |Cite
|
Sign up to set email alerts
|

Protein Adsorption into Mesopores: A Combination of Electrostatic Interaction, Counterion Release, and van der Waals Forces

Abstract: Bovine heart cytochrome c has been immobilized into the mesoporous silica host material SBA-15 in both its native folded and urea-unfolded state. The comparison of the two folding states' behavior casts doubt on the commonly used explanation of cytochrome c adsorption, that is, the electrostatic interaction model. A detailed investigation of the protein binding as a function of pH and ionic strength of the buffer solution reveals the complex nature of the protein-silica interaction. Electrostatic interaction, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 46 publications
2
59
0
1
Order By: Relevance
“…Similar values of the ES potential were observed when using liposomes as a template to build PE nanocapsules [146]. Note also the properties of electrostatically driven adsorption of proteins onto highly charged silica surfaces and inside porous substrates, see [147][148][149]. At all these conditions, the nonlinear ES effects can come into play.…”
Section: Discussionsupporting
confidence: 63%
“…Similar values of the ES potential were observed when using liposomes as a template to build PE nanocapsules [146]. Note also the properties of electrostatically driven adsorption of proteins onto highly charged silica surfaces and inside porous substrates, see [147][148][149]. At all these conditions, the nonlinear ES effects can come into play.…”
Section: Discussionsupporting
confidence: 63%
“…A PDI less than 0.25 suggested that the suspension had a narrow distribution (Ibrahim et al 2014;Ninjbadgar et al 2015). During the milling process, nanoparticle agglomeration was mainly caused by van der Waals forces and electrostatic interactions (Rance et al 2010;Moerz and Huber 2015). For anionic surfactant, SDS could provide sufficient electric charge to induce electrostatic repulsion for the suspended particles (Teeranachaideekul et al 2008).…”
Section: Preparation Of the Azoxystrobin Nanosuspensionmentioning
confidence: 99%
“…It has also been used in the adsorption/immobilization of carbonic anhydrase [23] and biomolecules such as bovine serum albumin [24][25][26], lysozyme [27][28][29], myoglobin [30], lipase [31][32][33], cellulose [34], trypsin [26,35], aminoacids [36], laccase [37], glucose oxidase [38], cytochrome c and xylanase [39,40].…”
Section: A N U S C R I P Tmentioning
confidence: 99%